Penerapan Prinsip Kehati-Hatian dalam Pembuatan Akta Jual Beli oleh Pejabat Pembuat Akta Tanah (PPAT) Berdasarkan Fakta Materiil: (Studi Kasus Putusan Nomor : 248/Pid.B/2022/PN Jkt Brt) - Merah Darwin; Adnan Hamid; Tetty Samosir (Jurnal Hukum Lex Generalis, 2025)
In the context of sale and purchase deeds, which are one of PPAT’s primary legal products, the application of prudence should not be limited to formal truth—truth based on fulfilling formal or procedural requirements as stipulated by law—without considering the substance or material facts behind it. These material facts are obtained through the application of material truth, which refers to efforts to ensure that all aspects of the deed-making process reflect actual reality so that the resulting legal product achieves perfection in both substance and future impact. Material truth, which produces material facts, also plays a crucial role in legal reform and legal certainty—two inseparable elements in legal practice. From a legal reform perspective, material truth that produces material facts is an urgent need, as there are currently no specific regulations governing its application in the deed-making process. Meanwhile, from a legal certainty standpoint, material facts have a direct impact on preventing potential disputes, both in the short and long term. Thus, applying material truth to obtain material facts in the preparation of sale and purchase deeds can be a concrete step toward creating legal products that are not only dispute-free but also provide justice and sustainable benefits for all related parties. Therefore, a review of existing regulations concerning the duties, obligations, and authorities of PPAT is necessary.